Kemelitan Penegakan Hukum terhadap Hak Kebebasan Berpendapat - Syafaat Anugrah Pradana; Rusdianto Sudirman; Muh. Andri Alvian (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri (IAIN) Parepare, 2022)
The state is obliged to provide protection and fulfillment of the right to freedom of expression, but these ideals still try to pursue an ideal position towards law enforcement and human rights in accordance with the orders of Pancasila and the 1945 NRI Constitution. Therefore, this study aims to find out and analyze the problems of human rights enforcement in the concept of a legal state in terms of the right to freedom of expression. The method used in this study is a normative research method with a conceptual approach (conseptual approach). The results showed that law enforcement against free speech was reviewed in three aspects, namely legal structure, legal substance, and legal culture. These three aspects became the source of findings of fundamental problems, so that the revision of the law on electronic information and transactions, the restorative justice approach, and the development of national character became a necessity in the context of enforcing the right to free speech in Indonesia in accordance with Pancasila and the 1945 NRI Constitution.